2011
DOI: 10.1080/08927014.2011.582642
|View full text |Cite
|
Sign up to set email alerts
|

Development of silver-containing austenite antibacterial stainless steels for biomedical applications Part I: microstructure characteristics, mechanical properties and antibacterial mechanisms

Abstract: The as-quenched (AQ) microstructure of the Ag-containing alloys was found to be essentially a mixture of austenite (γ) and Ag phases. The Ag phase precipitates had a face-centered-cubic structure and lattice parameter a = 4.09 Å. When the alloy contained Ag ≥0.2 wt%, the mechanical properties were slightly enhanced because of the precipitate strengthening by the Ag phase precipitates. Moreover, the Ag-containing alloys exhibited ductile fracture after tensile testing. The results of an antibacterial test revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Moreover, recent studies found D Tie et al Antibacterial biodegradable alloys that silver is also effective in the treatment of some extreme microbes, such as methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) -that are famous 'superbugs' that cannot be killed by most antibiotics (Nanda et al, 2009;Saravanana et al, 2010). The latest progress on silver coatings and magnesium-silver alloys for antibacterial application showed satisfactory results as well (Paton et al, 2010;Huang et al, 2011;Necula et al, 2011), while metallic and alloyed silver did not show any cytotoxicity in silver-containing medical devices (Bosetti et al, 2002). A small amount of silver content in alloys or coatings was also reported to improve cytocompatibility and cell viability (Bosetti et al, 2002;Hardes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies found D Tie et al Antibacterial biodegradable alloys that silver is also effective in the treatment of some extreme microbes, such as methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) -that are famous 'superbugs' that cannot be killed by most antibiotics (Nanda et al, 2009;Saravanana et al, 2010). The latest progress on silver coatings and magnesium-silver alloys for antibacterial application showed satisfactory results as well (Paton et al, 2010;Huang et al, 2011;Necula et al, 2011), while metallic and alloyed silver did not show any cytotoxicity in silver-containing medical devices (Bosetti et al, 2002). A small amount of silver content in alloys or coatings was also reported to improve cytocompatibility and cell viability (Bosetti et al, 2002;Hardes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium-based biodegradable alloys are experiencing a great interest as implant materials suitable for bone and cardiovascular applications (Staiger et al, 2006;Erbel et al, 2007;Witte et al, 2008;Pollock, 2010;Witte, 2010;Huehnerschulte et al, 2012). They show good cytocompatibility (Witte et al, 2006;Witte et al, 2007) and similar mechanical properties to bone .…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the antibacterial ability and mechanism of Ag containing alloys or composites [10,23,32,38,39] most of literatures conclude that Ag + -ions-release causes the bacteria-inhibiting effect. In this study, YSZ-Ag composites exhibited significant inhibiting effect when 0.5 wt% Ag was added.…”
Section: The Effect Of Ag-ions-release On Bacteria Inhibitingmentioning
confidence: 97%
“…With regard to the concentration of Ag ions needed to inhibit bacteria, a minimum concentration of 30-125 ppb has been proposed, for certain bacterial strains [37]. In our previous study [10], 316L stainless steel containing 0.1 wt% Ag exhibits poor antibacterial activity because only trace amounts of Ag + ions (<15 ppb) are released into the bacterial suspension.…”
Section: The Effect Of Ag-ions-release On Bacteria Inhibitingmentioning
confidence: 98%
See 1 more Smart Citation